Consumers' desire to use augmented reality applications - Soon, Pei Shan * (2021)
The extant literature on augmented reality (AR) in marketing has mostly focused on the cognitive aspect. Existing research seems to overlook the importance of understanding consumers’ emotional processes associated with the use of AR applications, particularly the relationship between positive emotions elicited by AR applications and the desire to use AR applications. Therefore, in view of the fact that little existing research on AR has included emotion variables and has yet to delve into the emotional process, this study aims to examine consumers’ desire towards AR applications by exploring the pattern of positive emotions elicitation resulting from their use. By reviewing prominent models from the field of consumer behaviour, psychology, technology acceptance, and self-service technology, this study addresses a meaningful literature gap through looking at the impact of the role of expressive, physiological, affective, motivational, and cognitive emotions on the desire to use AR applications. Two experimental studies (N = 224; N = 200) were conducted wherein two treatments were used for each study. The experimental groups explored products using AR applications while the control groups browsed the mobile website of the same brand without AR features. Data was collected by the researcher herself. Researcher recruited university students and staff to participate in the experiments during their free time. The findings showed that the use of AR applications induces positive expressive emotions which elicit physiological, affective, motivational, and cognitive emotions. Two out of four components of the elicited emotions (affective and motivational) generate a desire to use an AR application and in turn positively lead to a willingness to purchase a product. This study provides several theoretical contributions. The first theoretical contribution is an explanation of the emotional processes involved when using AR applications. The next theoretical contribution is based on the inclusion of positive emotions variable in the research models. Third, this study extends prior research on consumer behaviour and it deepens the theory of technology use in general. The fourth theoretical contribution is the integration of emotional antecedents, motivational mediators, and behavioural outcomes derived through the use of AR enabled applications. The last theoretical contribution is providing an understanding of the functions and mechanisms of positive emotions resulting from interactions with AR applications. In terms of managerial implications, this study shows that it is vital for both developers and marketers to understand that inducing positive expressive emotions is fundamental in designing an AR application. The results also imply that AR applications have the potential to become effective marketing tools for companies, particularly in achieving bottom-of-funnel objectives such as willingness to purchase a product.